ANALYSIS OF THE IMPACT OF PARENTING PATTERNS OF PARENTS WHO GET MARRIED AT A CHILDHOOD AGE ON CHILD GROWTH AND DEVELOPMENT (CASE STUDY OF JELANTIK VILLAGE, JONGGAT DISTRICT) - Istilam Istilam (JOETAL: Journal of Education, Teaching and Learning, 2025)
The purpose of this study is to determine the impact of parenting patterns resulting from child marriage and how parenting patterns are carried out by parents or families who are still married at a young age. The research method used was Qualitative type of research with a case study approach. The data collection methods used observation, interviews and documentation. The data analysis method used data reduction, data display and drawing conclusions. The results of the study (1) the parenting patterns used by parents who have early marriages in Jelantik Village tend to be different, namely authoritarian parenting patterns, democratic parenting patterns, permissive parenting patterns and mother-dominant parenting patterns. (2) The impact of parenting patterns of parents namely psychosocial impacts, nutritional fulfillment and child growth and development. For parents who tend to apply an authoritarian parenting pattern, the impact on children's psychosocial makes children tend to be more closed to their environment, while the psychosocial impact on children for parents who tend to apply a democratic parenting pattern makes children confident, disciplined and obey existing rules. The psychosocial impact for children with a permissive parenting pattern can make children emotional and must be followed by all their wishes. The impact of fulfilling nutritional intake in children, some parents pay attention to their children's daily nutritional intake, while some parents tend to pay less attention to the nutritional intake obtained by children in their daily lives so that some children are indicated to experience stunting.